Associations between multiple heavy metals exposure and glycated hemoglobin in a Chinese population. (January 2022) - Cai, Jiansheng; Li, You; Liu, Shuzhen; Liu, Qiumei; Min xu,; Zhang, Junling; Wei, Yanfei; Mo, Xiaoting; Lin, Yinxia; Tang, Xu; Mai, Tingyu; Mo, Chunbao; et al.
Abstract: Background: Heavy metals may play an important role as environmental risk factors in diabetes mellitus. This study aimed to explore the association of HbA1c with As, Cd, Cu, Ni, Pb, and Zn in single-metal exposure and multi-metal co-exposure models. Methods: A cross-sectional study involving 3472 participants was conducted. Plasma concentrations of heavy metals were determined by inductively coupled plasma mass spectrometry. We estimated the association of each metal with HbA1c by linear regression. Potential heterogeneities by sex, age, and smoking were investigated, and metal mixtures and interactions were assessed by the Bayesian kernel machine regression (BKMR). Results: In linear regression, Cu (β = 0.324, p < 0.05) and Ni (β = −0.19, p < 0.05) showed significant association with HbA1c in all participants. In BKMR analyses, all exposure–response relationships were approximately linear. Cu was significantly and positively associated with HbA1c levels in overall participants, women, participants aged 60 years old and above, and nonsmokers. Ni was significantly and negatively associated with HbA1c levels in overall participants. We did not observe the overall effect of plasma metal mixtures on HbA1c or the interaction effect of the metals on HbA1c. Conclusion: Cu was positively correlated with HbA1c, whereas Ni was negatively correlated with HbA1c, when evaluated individually or in a metal mixture. Additional studies are necessary to confirm these correlations and to control for exposure to different metals in the general population. Graphical abstract: Image 1 Highlights: Plasma Cu was positively correlated with HbA1c. Plasma Ni was negatively correlated with HbA1c. Low levels of As, Cd, and Pb exposure may not be associated with HbA1c.